Perfil cromatográfico dos extratos brutos das sementes de Annona muricata L. e Annona squamosa L. através da cromatografia líquida de alta eficiência. - Lima, Milena Duarte (2007)
Phytochemical studies performed previously under laboratory conditions using the species Annona muricata resulted in the extracion of a mixture of acetogenins, which is a class of substances very difficult to separate, despite its large spectra of biological activities. The insectidal properties of this class of compounds which is exclusive of the Annonaceae family have drive our attention to its use against the mosquito Aedes aegypti. The methodology used to extract acetogenins from Annona muricata and Annona squamosa crude ethanolic extracts was the reversed phase High Performance Liquid Chromatography (HPLC). By means of this technique seven acetogenins, two from seeds of Annona muricata AMS2 (tR=8,5), AMS3 (tR=9,5) and five from seeds of Annona squamosa ASS2A (tR=4,5), ASS2B (tR=5,0), ASS2C (tR=5,5), ASSX (tR=7,5) and ASS3 (tR=8,0) were extracted. Based on the triangle of solvent selectivity an special mobile phase composition was developed for reference compound ASS3 from seeds of A. squamosa a betted ACN/MeOH/THF/H2O 16:66:4:14 v/v. Among the seven acetogenins extracted from the seeds of Annona muricata and Annona squamosa, only two: AMS2 and ASS3 had their chemical structures identifield as such: Anonacina and Squamocina A, also know as Anonine I, with the aid of nuclear magnetic ressonance (1H and 13C) and infrared spectroscopy. The molecular ion of the identifield acetogenins were determined by mass spectrometry using the chemical ionization as a technique.